Evaluation of Pichia pastoris-Expressed Recombinant Rhoptry Protein 2 of Toxoplasma gondii for Its Application in Diagnosis of Toxoplasmosis - Chang, P.Y.; Fong, M.Y.; Nissapatorn, V.; Lau, Y.L. (2011)
Rhoptry protein 2 (ROP2) of Toxoplasma gondii is a rhoptry-secreted protein that plays a critical role in parasitophorous vacuole membrane formation during invasion. In previous studies, ROP2 has been shown to be efficient in triggering humoral and cell-mediated responses. High immunogenicity of ROP2 makes it a potential candidate for diagnosis and vaccination against toxoplasmosis. In this study, the ROP2 gene was cloned into pPICZ alpha A expression vector and extracellularly expressed in the yeast Pichia pastoris, which has numerous advantages over other expression systems for eukaryotic proteins expression. The effectiveness of the secreted recombinant ROP2 as a diagnosis agent was assessed by Western Blot with 200 human serum samples. Recombinant ROP2 reacted with toxoplasmosis-positive human serum samples and yielded an overall sensitivity of 90 and specificity of 95. However, recombinant ROP2 is a better marker for detection of IgG (91.7) rather than IgM (80).